2017
DOI: 10.1016/j.apjtm.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Bougainvillea spectabilis flowers extract protects against the rotenone-induced toxicity

Abstract: These data indicate that B. spectabilis flowers extracts exert protective effect against the toxic effects of rotenone on brain, liver and kidney. B. spectabilis flowers extracts decreased brain lipid peroxidation and prevented neuronal death due to rotenone and might thus prove the value in treatment of Parkinson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Our data also show that rotenone can result in significant inhibition of BChE activity in the brain tissues which is in agreement with previous observations [54]. Rotenone was also demonstrated…”
Section: Rossupporting
confidence: 93%
See 2 more Smart Citations
“…Our data also show that rotenone can result in significant inhibition of BChE activity in the brain tissues which is in agreement with previous observations [54]. Rotenone was also demonstrated…”
Section: Rossupporting
confidence: 93%
“…Excessive nitric oxide can result in inhibition of mitochondrial respiration, and cellular energy depletion [52,53]. Rotenone also induces a state of neuroinflammation in the brain tissue [47,54]. This toxicant has been shown to increase the expression of tumor necrosis factor-alpha (TNF-α) as well as the level of monocyte chemoattractant protein-1 (MCP-1) [47] and interleukin-1β [54] in the rat brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to induce PD in rats, rotenone (ROT, Sigma-Aldrich, Poznań, Poland) was injected subcutaneously once daily for 35 days in a dose of 1.3 mg/kg body weight. The doses and schedule of ROT used in the present study were established based on our results from preliminary studies, and they are similar to those previously described in published reports [33,39,57,65] with slight modifications (Figure 10). Forty rats (cohort #1) were divided randomly into four groups, with 10 animals in each.…”
Section: Experimental Designmentioning
confidence: 75%
“…Both extracts caused further inhibition of PON-1 activity while the yellow extract resulted in further inhibition of BChE activity. Histopathological studies indicated that both extracts protected against brain, liver, and kidney damage caused by the toxicant [ 52 ].…”
Section: Pharmacological Activitymentioning
confidence: 99%